THE ROLE OF DIGITAL MARKETING IN THE BATIK INDUSTRY IN FACING INTERNATIONAL FASHION INDUSTRIALIZATION 5.0 - Arsyad, Abyan; Ajeng, Sulviani; Septiani, Cindi; Erawati, Dedet (Ridwan Institute, 2024)
Digital marketing has become a hot topic in the last few decades. The purpose of this study is to find out how the function of digital marketing in the Batik sector is to maintain it in the face of global fashion trends. A qualitative descriptive method was used in this study to explore the role of emerging digital marketing tools in promoting traditional industries like Batik. Data was collected from observations, interviews, research-related documents, and literature reviews. The results showed that the use of social media and websites was particularly useful for identifying various digital marketing strategies used by both domestic and foreign companies. Digital marketing can be used to retain customers, encourage them to develop preferences, increase sales, and ultimately increase revenue. The use of digital platforms can be a tool that sellers can use to amplify their business message, and with digital marketing it can reach a wider range of customers so that business development can be faster. Future studies could explore the potential impact of newer or underutilized marketing tools (e.g., AI-powered marketing tools, augmented reality in fashion marketing) on traditional industries such as Batik, especially in niche markets. Future research could explore how digital marketing can effectively promote sustainable Batik practices, highlighting eco-friendly production methods and responsible consumerism, which may resonate with global fashion trend.